The Efficiency of Mechanized Mineral Processing Techniques to Recover Tin and Tantalum Ores. Case Study: Nyamatete Concession, Rwanda - UWIZEYIMANA, Jules; RWABUHUNGU RWATANGABO, Digne Edmond; IMANIRAFASHA, Esperance; BARAYAGWIZA, Vincent; HATEGEKIMANA, Francois (GeoScience Engineering, 2022)
Mining activities have resulted in a large volume of tailings containing a certain proportion of lost minerals, making them a potential reprocessing opportunity, and information on tailings and mineral reprocessing is often scarce. In this study, a conceptual framework was established and used to produce meaningful information and knowledge from the tailings of the Nyamatete mine at HABATU Mining Company Limited (an ASM in Rwanda). Tailings particles were investigated based on the observed lithology to determine their distribution over the tailing dams, and a site-specific sampling approach and procedure were established. Sieving the collected samples, particle size analysis, and chemical analysis using XRF were chosen as methods for tailings characterization. Raw materials such as SnO2, minor Ta2O5, and Nb2O5 and elements of environmental importance such as Mn, Co, and as were observed but in small quantities are largely predominant in quartz vein, have been discovered in Nyamatete tailings. The comminution and gravity separation by mechanical reprocessing facilities improved Cassiterite recovery by 43.9 % compared to the artisanal processing method. SnO2 recovery of 19.4 % and 29.9 % with grades of 63.224 % and 76.6 % were obtained in pegmatite and quartz tailings respectively. According to a scoping study, the Habatu tailings have an appropriate grade, the valuable content occurs in a recoverable grain-size range, and the total ore amount scales with the required input for the reprocessing equipment. Tailings reprocessing with mechanized reprocessing equipment is advantageous because it improves efficiency while also treating the material with previously unknown quantities of ore, thereby significantly increasing the total recovery of processed Run of Mine. Keywords: Artisanal processing; Cassiterite; Coltan; Mechanized processing; Tailings.